The Effectiveness of Behavioral Counseling with Techniques of Modeling By Lesson Study Setting to Improve Endurance of Students - Khuzaimatul Jannah; Kadek Suranata; I Ketut Dharsana (RedwhitePress)
This research aims to improve students on task behavior by Behavioral Counseling with Techniques of Modeling By Lesson Study Setting. This research population is 59 students and research samples of 25 students with this type of research is quasi-experiments, pretest-postest control group design.From the analysis of tcount 14,875 > ttable 2,063 so that H0 is rejected and Ha be accepted. So, there is a significant difference attitude complete the work at grade X SMA Negeri 4 Singaraja before and after using the theory of behavioral counseling with the technique of modeling. Behavioral counseling can be summed up with the modeling techniques through lesson study effectively to improve the attitude of complete the work.